The Oxford handbook of business and the natural environment - Bansal, Pratima; Hoffman, Andrew J. (Oxford Oxford University Press, 2013)
Environmental issues now loom large on the social, political, and business agenda. Over the past four decades, "corporate environmentalism" has emerged and been constantly redefined, from regulatory compliance to more recent management conceptions such as pollution prevention, total quality environmental management, industrial ecology, life cycle analysis, environmental strategy, environmental justice, and, most recently, sustainable development. As a result, understanding the intersection of business activity and environmental protection has become increasingly complex, and there has emerged a focus in academic research on business decision-making, firm behavior, and the protection of the natural environment. This handbook reviews the state of the field as it grows into a mature area of study within management science, its achievements, and its future avenues of research. It brings together original contributions in the field along several lines of enquiry. The first six focus on disciplines as delineated in contemporary business schools: business strategy; policy and non-market strategies; organizational theory and behavior; operations and technology; marketing; and accounting and finance. The seventh section reviews emergent and associated perspectives, whilst a concluding section, written by long-standing leaders in the field, discusses the future outlook for research
Keywords: Empresas -- Aspectos ambientales; Gestión ambiental; Desarrollo sostenible -- Aspectos ambientales; Gestión de empresas -- Aspectos ambientales